Feeding, caregiving practices, and developmental delay among children under five in lowland Nepal: a community-based cross-sectional survey - Sophiya Dulal; Audrey Prost; Surendra Karki; Dafna Merom; Bhim Prasad Shrestha; Bishnu Bhandari; Dharma S. Manandhar; David Osrin; Anthony Costello; Naomi M. Saville (BMC, 2022)
Abstract Background Nurturing care, including adequate nutrition, responsive caregiving and early learning, is critical to early childhood development. In Nepal, national surveys highlight inequity in feeding and caregiving practices for young children. Our objective was to describe infant and young child feeding (IYCF) and cognitive and socio-emotional caregiving practices among caregivers of children under five in Dhanusha district, Nepal, and to explore socio-demographic and economic factors associated with these practices. Methods We did a cross-sectional analysis of a subset of data from the MIRA Dhanusha cluster randomised controlled trial, including mother-child dyads (N = 1360), sampled when children were median age 46 days and a follow-up survey of the same mother-child dyads (N = 1352) when children were median age 38 months. We used World Health Organization IYCF indicators and questions from the Multiple Indicator Cluster Survey-4 tool to obtain information on IYCF and cognitive and socio-emotional caregiving practices. Using multivariable logistic regression models, potential explanatory household, parental and child-level variables were tested to determine their independent associations with IYCF and caregiving indicators. Results The prevalence of feeding indicators varied. IYCF indicators, including ever breastfed (99%), exclusive breastfeeding (24-hour recall) (89%), and vegetable/fruit consumption (69%) were common. Problem areas were early initiation of breastfeeding (16%), colostrum feeding (67%), no pre-lacteal feeding (53%), timely introduction of complementary feeding (56%), minimum dietary diversity (49%) and animal-source food consumption (23%). Amongst caregiving indicators, access to 3+ children's books (7%), early stimulation and responsive caregiving (11%), and participation in early childhood education (27%) were of particular concern, while 64% had access to 2+ toys and 71% received adequate care. According to the Early Child Development Index score, only 38% of children were developmentally on track. Younger children from poor households, whose mothers were young, had not received antenatal visits and delivered at home were at higher risk of poor IYCF and caregiving practices. Conclusions Suboptimal caregiving practices, inappropriate early breastfeeding practices, delayed introduction of complementary foods, inadequate dietary diversity and low animal-source food consumption are challenges in lowland Nepal. We call for urgent integrated nutrition and caregiving interventions, especially as interventions for child development are lacking in Nepal.